PURCHASING DECISION EFFORTS AT YOEDHA REKLAME KALILARANGAN SURAKARTA REVIEWED FROM THE ASPECT OF MARKETING MIX - Septiana Novita Dewi; Sinta Patma Dwijayanti (KELOLA, 2019)
The purpose of this study was to empirically analyze the effect of product, price, location, promotion and distribution on purchasing decisions on Yoedha Reklame Kalilarngan. The population in this study is customersat Yoedha Reklame Kalilarangan. The sample of this study was taken as many as 90 samples used as respondents. The analysis method in this study consisted of testing instruments, classic assumption tests, multiple linear regression analysis, t test, F test and ????2  test. Based on the results of the analysis show that the validity and reliability test on all items asked questions proved to be valid and reliable. The classic assumption test results show that this study does not occur multicollinearity, there is no heteroscedasticity, autocorrelation in the regression model and normally distributed. The results of multiple linear regression coefficients show thatthe product variable has a negative effect and the variable price, location, promotion, distribution has a positive effect on purchasing decisions in Yoedha Reklame Kalilarangan. The results of the t test show that the product has a negative and insignificant effect, for prices, promotions and distribution to have a positive and significant effect, while the location has a positive and insignificant effect on purchasing decisions at Yoedha ReklameKalilarangan. The results of the F test indicate that there is a significant influence between product, price, location, promotion and distribution together on purchasing decisions in Yoedha Reklame Kalilarangan.Meanwhile, the results of the ????2  test (coefficient of determination) are known that product variables, price, location, promotion and distribution are able to explain 48.4% of the purchase decision variable, while the remaining 51.6% is explained by other variables such as brand image, brand image, and consumer loyalty.